Assessment and correlation of vibrio parahaemoliticus in pond water from aquaculture farm - Nurulhuda Najihah, Binti Zainal Abidin (Universiti Malaysia Sarawak (UNIMAS), 2013)
In this study, the occurrence of Vibrio parahaemolyticus in aquaculture samples were determined by using most probable number (MPN) method and polymerase chain reaction (PCR) method. One hundred and thirty five samples were collected from two different ponds in the selected aquaculture farm . Upon analysis, the occurrences of V parahaemolyticus were 25% in Pond 1 and 29% in Pond 14. Moreover, this study also relates the occurrence of V parahemolyticus with the environmental variables such as temperature, salinity and pH. The statistical analysis showed that the occurrence of V parahemolyticus were positively and significantly related with pH but negatively and not significantly related with both temperature and salinity. The results from this study concluded that there were V parahemolyticus occurrence in the Bako Aquaculture Farm, but there is no significant difference between concentration of V parahaemolyticus in Pond 1 and Pond 2. Moreover, the environmental parameter such as pH, salinity and temperature was not significantly correlated with the concentration of V parahaemolyticus in the water samples.